2014
DOI: 10.1093/czoolo/60.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating preservation medium for the storage of DNA in African lion Panthera leo faecal samples

Abstract: Lion faecal samples, collected in the field between 1 hour to 1 week after defecation were preserved in three different media (ethanol, ASL buffer and Two-step storage). The aim was to determine which faecal DNA field preservation method best enhances PCR amplification success. Samples stored in ethanol showed a significantly higher amplification success of microsatellite loci than samples stored in the other two media. In contrast, amplification success of a mitochondrial locus was similar among the samples s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…Similar to our results, EtOH scored the highest in the study on brown bear (Murphy et al 2002), Eurasian badger (Frantz et al 2003), lion (Tende et al 2014), or was equally high as the other methods in the study on primate scats (Whittier et al 1999), gorilla (Roeder et al 2004), and coyote (Panasci et al 2011), although the preservation methods evaluated in these studies were different. These findings revealed that EtOH was a good preservation buffer for fecal samples, irrespective of the diet of the species and this method could be used in either tropical or temperate weather (Roeder et al 2004;Tende et al 2014).…”
Section: Manuscript To Be Reviewedsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to our results, EtOH scored the highest in the study on brown bear (Murphy et al 2002), Eurasian badger (Frantz et al 2003), lion (Tende et al 2014), or was equally high as the other methods in the study on primate scats (Whittier et al 1999), gorilla (Roeder et al 2004), and coyote (Panasci et al 2011), although the preservation methods evaluated in these studies were different. These findings revealed that EtOH was a good preservation buffer for fecal samples, irrespective of the diet of the species and this method could be used in either tropical or temperate weather (Roeder et al 2004;Tende et al 2014).…”
Section: Manuscript To Be Reviewedsupporting
confidence: 88%
“…This renders the conclusion of genetic studies unreliable and reduces the confidence in inferring such results for formulating management and conservation strategies (Pompanon et al 2005). Several investigations suggest that careful choice of microsatellite loci and the method used for feces preservation could enhance the genotyping success and feasibility of the use of fecal samples in such studies (Broquet et al 2007;Tende et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of storage methods have been used and tested for efficacy, including desiccation, freezing, or storage in buffers or ethanol. In most studies, pure ethanol (i.e., 95–100%) works similarly to or better than other methods for shorter storage periods and can substantially outperform them during extended storage periods (Murphy et al , Frantz et al , Piggott and Taylor , Beja‐Pereira et al , Panasci et al , Tende et al ). However, acquiring, storing, and transporting sufficient quantities of ethanol for sample storage can be difficult in remote field conditions.…”
mentioning
confidence: 99%
“…Significant improvements have been reported based on fecal DNA analysis for both extraction and quantification of nucleic acids as part of genotyping and species identification (Kanthaswamy, Premasuthan, Ng, Satkoski, & Goyal, ). Molecular analysis of feces is a noninvasive method with a high degree of integrity and quality when using specific commercial kits for these complex matrices (Deshpande, Villarreal, & Mills, ; Ramón‐Laca, Soriano, Gleeson, & Godoy, ; Tende, Hansson, Ottosson, & Bensch, ). The main challenge of this study was to obtain DNA of good quality from fecal samples collected in the Atacama Desert.…”
Section: Discussionmentioning
confidence: 99%